Sistem Informasi Manajemen Pengajian Tahsin Al-Qur’an di Kota Medan - Alharis, Dimas Cholis; Nasution, Muhammad Irwan Padli (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
This research aims to overcome problems in the management of tahsin Al-Qur'an recitation activities. These recitation activities are often spread across various locations with different presenters and congregations, causing a lack of coordination and focus in the material and difficulties in finding a schedule for Al-Qur'an tahsil recitation activities because information about the recitation is not widely published. As a result, public interest in reciting tahsin directly decreased. The research method used is a qualitative method. Qualitative research methods are research approaches that aim to understand complex phenomena or problems in depth. Using qualitative research methods, researchers find needs and solutions to the problems faced. To overcome this problem, researchers built a website-based Tahsi Al-Qur'an Recitation Management Information System. This system allows managing activities and data digitally, reducing the time required to handle recitation activities to a large extent. Through this approach, the Management Information System can be an effective tool in improving the quality and efficiency of reciting the tahsin of the Al-Qur'an. This system's activity management process includes functions such as publishing recitation activities, managing recitation schedules, and detailed information regarding the material and presenters who will conduct the recitation. The existence of this system is a solution to the problem of managing recitation activities and the problem of publishing information about the recitation of the tahsin of the Qur'an, as well as increasing public interest in the recitation of tahsin.